Edukasi dan Pendampingan Gizi Keluarga sebagai Upaya Penanggulangan Stunting di Puskesmas Duren Sawit Jakarta Timur - Istianah, Isti; Srimiati, Mia; Ratnayani, Ratnayani; Agestika, Lina; Khasanah, Tri Ardianti; Alfaz, Ni'ma Ghida; Winantoro, Dimas Wahyu; Fayasari, Adhila (Jurnal Abdimas Kesehatan (JAK), 2025)
Stunting is a chronic nutritional problem affecting child growth and remains a challenge in East Jakarta, particularly in Pondok Kopi and Klender. This program aimed to improve the nutritional status of stunted children through family-based nutrition education and assistance. Activities were conducted from September to November 2023 in the Duren Sawit Public Health Center area. Interventions included nutrition education, monitoring of weight and height, dietary intake recording, and home environment observation. Results showed improved maternal knowledge about food variety and nutritional status improvements in some children. Approximately 20–25% showed progress in weight-for-age, height-for-age, and weight-for-height indicators. Despite fluctuations, the interventions had a positive impact on child growth. Environmental factors also influenced nutrition, so sanitation education was provided. The program demonstrated that family-based education and assistance can help reduce stunting, though continued and personalized interventions are still needed.